Implementation of Education Quality Assurance in Order to Improve School Quality at SMK Mekarmukti Garut - Sudarajat AM; Soeganda Priyatna; Ida Tedjawiani; R. Supyan Sauri (CV. AFDIFAL MAJU BERKAH, 2021)
This research describe about Education Quality Assurance System is the entire function of education management that develops the duties and responsibilities in measuring and assessing the fulfillment of quality standards. SMK Mekarmukti Garut is one of the schools that has implemented the Primary and Secondary Education Quality Assurance System, which is in accordance with the established indicators, namely the Eight National Education Standards.